2017
DOI: 10.24017/science.2017.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of anemia among pregnant women in primary health centers/Erbil City

Abstract: Anemia in pregnancy is a major public health problem, especially in developing countries. Nutritional anemia is the most common type of anemia worldwide and mainly includes iron, folic acid, vitamin B12 and vitamin C deficiencies. Iron deficiency contributes to half of the burden of anemia globally. The objectives of this study were to find out the prevalence and severity of anemia among pregnant women. A descriptive study was conducted on 600 pregnant women, during the period October 2015 to November 2016 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…According to the WHO recommendations in 2017, the global percentage of women of reproductive age suffering from anemia is (33%). More than one-fifth of our study participants had moderate anemia, while studies by al Shawi et al (2012) Baghdad and Abdulwahid & Ahmed (2017) in Erbil/Iraq included 600 pregnant women which they founds that found that half of studied pregnant women of reproductive age suffer from anemia, their results are higher than the global rates and our results. The reasons for these differences might be related to a variation in study methodology.…”
Section: Discussioncontrasting
confidence: 70%
“…According to the WHO recommendations in 2017, the global percentage of women of reproductive age suffering from anemia is (33%). More than one-fifth of our study participants had moderate anemia, while studies by al Shawi et al (2012) Baghdad and Abdulwahid & Ahmed (2017) in Erbil/Iraq included 600 pregnant women which they founds that found that half of studied pregnant women of reproductive age suffer from anemia, their results are higher than the global rates and our results. The reasons for these differences might be related to a variation in study methodology.…”
Section: Discussioncontrasting
confidence: 70%
“…Since pregnancy is considered as one of the most important periods in a woman’s life [ 7 ], iron deficiency anemia (IDA) has dangerous effects on mother and fetus and reduces fertility, preterm delivery, severe neonatal birth weight, increased spontaneous abortion, increased fetal mortality and postpartum hemorrhage [ 8 , 9 ]. In addition, the consequences of anemia in pregnant women affect the social and economic development of individuals [ 10 ]. Anemia can be caused by iron deficiency, impaired absorption, iron loss, or increased need for iron [ 11 ].…”
Section: Introductionmentioning
confidence: 99%